Respuesta :

Answer:

a) -x(4[tex]x^{2}[/tex] -x +1)

b) 4[tex]x^{3}[/tex] (x-1)

c) -12[tex]x^{2}[/tex] - 3x + 3

Step-by-step explanation:

Most of it is really just a matter of substituting expressions in. here's how i did it:

f(x) = x-1

g(x) = 4[tex]x^{2}[/tex]

a) (f-g) x [tex]x[/tex]

= (x - 1- 4[tex]x^{2}[/tex]) x [tex]x[/tex]

= x(- 4[tex]x^{2}[/tex]+x-1)

= -x (4[tex]x^{2}[/tex] - x + 1)

*you can take the negative out of the bracket or not, i did though - just makes it neater. They are both right.

b) (fxg) x [tex]x[/tex]

= (4[tex]x^{2}[/tex](x-1)) x [tex]x[/tex]

= 4[tex]x^{3}[/tex] (x-1)

*just bring the x to the front and times it with the 4[tex]x^{2}[/tex]

c) (f+g) x -3

= (x - 1 + 4[tex]x^{2}[/tex]) x -3

= -3 (4[tex]x^{2}[/tex] + x -1)

= -12[tex]x^{2}[/tex] - 3x + 3

*just bring the -3 to the front and times it with the whole bracket to expand since it said evaluate

Hope that helped : )